Analysis of the Effect of Archive Arrangement, Infrastructure and Competency of Archive Officers on Work Effectiveness at the Office of Highways and Construction Development of North Sumatra Province - Suyanto Suyanto; Rudi Salam Sinaga; Maksum Syahri Lubis (Budapest International Research and Critics University, 2021)
This study aims to analyze the Effect of Archive Arrangement, Infrastructure and Competency of Archive Officers on Work Effectiveness at the Office of Highways and Construction Development of North Sumatra Province. This stud use quantitative approach. Based on the F test, it is known that the calculated F value is 3.342 and the F table value at 5% alpha is 2.86. Thus, the Fcount value (3.342) > F table (2.86) with a significance level of 0.030 < 0.05, meaning that together or simultaneously the variables of Archive Arrangement (X1), Infrastructure (X2) and Archives Officer Competence (X3) have a positive and significant effect on Work Effectiveness.The relationship between the arrangement of archives, infrastructure and the competence of archiving officers on the effectiveness of work in the Department of Highways and Construction of North Sumatra Province that the R Square value obtained is 0.218 or 21.8%. This shows the ability of the Archives Arrangement variable (X1), Infrastructure (X2) and Archive Officer Competence (X3) simultaneously or together to affect Work Effectiveness by 21.8%.